The Effect of Tax Sanctions, Issuance of Tax Assesments and Tax Collection on the Level of Taxpayer Compliance - Dwi Dewianawati; Sari Rahayu; Poppy Meilina Dian Hastuti; Agus Sunaryo (Sekolah Tinggi Ilmu Tarbiyah (STIT) Syekh burhanuddin, 2023)
of a document quickly and accurately, to determine its relevance to their interests, and thus to decide whether to read the document in its entirety. The Abstract should be informative and completely self-explanatory, provide a clear statement of the problem, the proposed approach or solution, and point out major findings and conclusions. The Abstract should be 100 to 200 words in length. The abstract should be The aim of this research is as follows: Testing the effect of tax sanctions on taxpayer compliance. Testing the effect of the issuance of a Tax Assessment Letter on the level of taxpayer compliance. Testing the effect of Tax Collection on the level of taxpayer compliance.The population in this research is Corporate Taxpayers, both directors and employees of these Corporate Taxpayers with an estimated population of approximately 200 people. The test used in this research is multiple linear regression. Based on hypothesis testing, the following conclusions are obtained: tax sanctions have a significant positive effect on taxpayer compliance, the issuance of a Tax Assessment Letter has a significant positive effect on taxpayer compliance, Tax Collection has a significant positive effect on the level of taxpayer compliance.